Pengaruh Pertambangan Batu Bara Terhadap Lapangan Pekerjaan: Penelitian - Bonaraja Purba; Ananda Sakinah; Ellyka Evitasari Purba; Khairunnisa Br Marpaung; Saskia Bella (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to evaluate the impact of coal exploitation activities on job creation in Indonesia. By applying a descriptive qualitative approach supported by quantitative data, this research examines the contribution of the coal sector in generating jobs, both direct and indirect. The findings indicate that the coal mining sector plays a significant role in labor absorption, covering key areas such as exploration, mining, and distribution, as well as supporting sectors like transportation, commercial services, catering, and accommodation. However, the nature of job opportunities created tends to be temporary due to factors such as the lifespan of the mines and fluctuations in global coal prices. Additionally, the implementation of modern technology tends to reduce the need for manual labor. Therefore, while coal mining can help reduce unemployment rates, excessive dependence on this sector It could lead to social and economic issues in the future. Therefore, there needs to be a strategy to diversify the economy and improve human resource capabilities so that community welfare is maintained after the closure of mining operations.